In Search for Femina Grata: Revanchist Urban Policies in a Historical District of Turkey - Mine EGBATAN (Ankara Araştırmaları Dergisi, 2021)
This study uses the analytical lens of the “revanchist city” to examine the neoliberal urban renewal processes in Ulus, a historical district in Ankara, Turkey’s capital city, in which prostitutes work. This study takes a comparative approach to examine the construction of femina grata by analyzing the law, practices, and political projects in relation to women in the radical modernity period of Turkey. It also analyzes current neoliberal revanchist interventions that have taken place in Ulus and looks at their gendered meanings in accordance with implemented urban renewal strategies. I mainly argue that neoliberal revanchist policies carried out in Ulus aim to cultivate city spaces for capital and attract families who engage in pious activities, and thus do not include those women and families who remain secular through the creation of a moment of “triple dualism.”